Breast Is (Viewed as) Best: Demonstrating Formula Feeding Stigma. (December 2020) - Moss-Racusin, Corinne A.; Schofield, Casey A.; Brown, Sophie S.; O'Brien, Kerry A.
Experimental research has not examined possible formula feeding stigma. We explored whether mothers encounter stigma resulting from infant feeding method and if formula feeding stigma is impacted by whether this feeding method was intended or unintended. Experiment 1 ( N = 252) exposed participants to a social media post in which a mother described intentionally breastfeeding, formula feeding, or did not mention a feeding method (control). Results provided the first experimental evidence of formula feeding stigma; the formula feeding mother was viewed less positively than the identical breastfeeding and control mothers, who were typically not perceived differently than one another. Experiment 2 ( N = 388) added conditions in which feeding methods were unintended. When feeding methods were intended, results replicated Experiment 1. However, when feeding methods were unintended, the pattern fully reversed; unintended formula feeders were viewed more positively than unintended breast-feeders. Further, women who formula fed were penalized when they did so intentionally, while those who breastfed were penalized when they did so unintentionally. This suggests that formula feeding stigma stems primarily from perceptions of feeding intentions (rather than the belief that breast milk is superior) because mothers who planned to formula feed were viewed more negatively than those who planned to breastfeed, regardless of whether babies actually received formula or breast milk. These results imply that caregivers, health care providers, and policy makers should be mindful of the potential for pro-breastfeeding rhetoric to be associated with formula feeding stigma (with potential consequences for the health of women and infants) and consider implementing interventions designed to reduce stigma and promote awareness of the safety and utility of proper formula use.